2012
DOI: 10.7150/ijms.4369
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil Prevents Tourniquet-Induced Arterial Pressure Increase in Elderly Orthopedic Patients under Sevoflurane/N2O General Anesthesia

Abstract: Aims: Prolonged tourniquet inflation produces a hyperdynamic cardiovascular response. We investigated the effect of continuous remifentanil infusion on systemic arterial pressure, heart rate, and cardiac output changes during prolonged tourniquet use in elderly patients under sevoflurane/N2O general anesthesia.Methods: Thirty female patients scheduled for knee replacement arthroplasty were infused with either remifentanil at a target organ concentration of 2.0 ng/mL (remifentanil group, n = 15) or saline (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…These changes persist until tourniquet deflation and poorly respond to analgesic drugs or increasing the depth of anesthesia. Many interventions have been reported to reduce cardiovascular stress:[242526272829303132] Ketamine, dexmedetomidine, magnesium sulfate, clonidine, and remifentanil infusion.…”
Section: Systemic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes persist until tourniquet deflation and poorly respond to analgesic drugs or increasing the depth of anesthesia. Many interventions have been reported to reduce cardiovascular stress:[242526272829303132] Ketamine, dexmedetomidine, magnesium sulfate, clonidine, and remifentanil infusion.…”
Section: Systemic Effectsmentioning
confidence: 99%
“…Many techniques[27] like application of EMLA cream, infiltration with local anesthetics, use of wider cuff with lower inflation pressure, addition of opioids, clonidine, epinephrine along with local anesthetics in spinal block have been tried in order to decrease the incidence or severity of this pain but none has attained complete success in pain relief. Intravenous drugs,[242527282930313247] ketamine, dexmedetomidine, magnesium sulfate, clonidine remifentanil infusions have also been studied, and the only thing that works reliably is tourniquet deflation.…”
Section: Tourniquet Painmentioning
confidence: 99%
“…16 During lower extremity procedures, different agents such as dextromethorphan, clonidine, remifentanil, and ketamine were used to prevent tourniquet-induced pain. 11,[17][18][19] In a study that compared dextromethorphan and clonidine for blunting the tourniquet-induced cardiovascular response during lower extremity procedures under general anesthesia, it was demonstrated that preoperative oral clonidine significantly decreased systolic, diastolic, and mean arterial pressures. 20 The study of Park et al demonstrated that preoperative low dose ketamine administration (0.1 mg.kg -1 ) is effective in the treatment of tourniquetinduced hypertension for 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Fakat, hipotansiyon, PBK, solunum depresyonu ve artmış postoperatif ağrı gibi yan etkilere sahiptir. Ayrıca, hızlı etki başlangıcı apne ve kas rijiditesi gibi yan etkilere de neden olabilir (11) . (12) .…”
Section: Discussionunclassified